2016
DOI: 10.3847/0004-6256/152/5/119
|View full text |Cite
|
Sign up to set email alerts
|

From Order to Chaos in Earth Satellite Orbits

Abstract: We consider Earth satellite orbits in the range of semi-major axes where the perturbing effects of Earth's oblateness and lunisolar gravity are of comparable order. This range covers the medium-Earth orbits (MEO) of the Global Navigation Satellite Systems and the geosynchronous orbits (GEO) of the communication satellites. We recall a secular and quadrupolar model, based on the Milankovitch vector formulation of perturbation theory, which governs the longterm orbital evolution subject to the predominant gravit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 39 publications
4
61
0
1
Order By: Relevance
“…Increasing A/m and adding drag to the model basically 'shift' the curves to higher q 0 . However, the dependence on A/m and drag is much smaller at high inclinations, where the main dynamical mechanism responsible for reentry is the overlapping of lunisolar resonances, as found in recent studies (see Celletti et al 2016;Gkolias et al 2016).…”
Section: Discussionsupporting
confidence: 60%
“…Increasing A/m and adding drag to the model basically 'shift' the curves to higher q 0 . However, the dependence on A/m and drag is much smaller at high inclinations, where the main dynamical mechanism responsible for reentry is the overlapping of lunisolar resonances, as found in recent studies (see Celletti et al 2016;Gkolias et al 2016).…”
Section: Discussionsupporting
confidence: 60%
“…Anticipating a bit the next section, we are here interested in the dynamical mechanisms leading to transport; in particular we have not discriminated collisional orbits as we did in earlier work. As it has already been discussed several times and pointed out in several contributions [7,8,10], the inclination dependentonly resonances widen and develop chaos when ε is increasing, letting less and less room for invariant KAM tori. Eventually for a = 29, 600, there is a macroscopic chaotic component.…”
Section: Highly Resolved Phase-space Viewsmentioning
confidence: 69%
“…When invoking effective models, we always face the question of the relevance of the reduced model (how sound are the qualitative or quantitative informations derived from it). Gkolias et al [10] established the testimony of this doubly-averaged model against a singly-averaged approach. By simulating the two dynamics on different domains of the action-action, action-angle and angle-angle spaces 8 , we showed that dynamical features of interests were reproduced and in perfect agreement.…”
Section: Numerical Treatment Of the Equations Of Motionsmentioning
confidence: 99%
“…The nonnegligible collision risks posed by these LEO-GEO transiting spacecraft has motivated both theoretical study and practical implementation (Armellin et al, 2015;Colombo et al, 2015;Merz et al, 2015). Even for the, seemingly more simple, inclined, nearly circular orbits of the navigation satellites, no official guidelines exist, and recent analyses have shown that the problem is far too complex to allow of an adoption of the basic geosynchronous graveyard strategy (Rosengren et al, 2015;Daquin et al, 2016;Celletti et al, 2016;Gkolias et al, 2016;Rosengren et al, 2017;Skoulidou et al, 2017) Fig. 1.…”
Section: The Cataloged Space Debrismentioning
confidence: 99%
“…For near-Earth satellites the effects of these distant perturbing bodies are often negligible,comparison to that of the Earth's oblateness, but for satellite orbits that are very elongated or have semimajor axes of several Earth radii, these third-body gravitational perturbations can change the elements of the orbit to a measurable extent, albeit on longer timescales than the Earth's oblateness. Indeed, recent works suggest that the coupled resonant effects of the Earth's oblateness and lunisolar perturbations are the most important mechanisms for delivering high-altitude, Earth-orbiting satellites into regions where atmospheric drag can give lead to orbital decay (Upton et al, 1959;Breiter, 2001;Daquin et al, 2016;Gkolias et al, 2016). Hence, these perturbations are fully taken into account in our model (in an Nbody framework; i.e., without recourse to truncated Legendre expansions is done in averaged formulations).…”
Section: Dynamical Modelmentioning
confidence: 99%